Pelatihan Peningkatan Kualitas Pelaporan Keuangan Yayasan Berdasarkan Interpretasi Standar Akuntansi Keuangan 35 di Masjid Jami Al-Mujahidin Bintara Bekasi Barat - Lucyanda, Jurica; Weni Pratiwi, Monica; Iman Santoso, Berkah; Rudianto, Dudi; Annastasya Nurdini , Dinda; Fadhilah, Anisah; Taga, Charis (LPkM Universitas Bakrie, 2023)
The activity of community service aims to improve the quality of the Yayasan's financial statements using a digital technology based on the Interpretation of Financial Accounting Standards (ISAK) 35 at the Yayasan Masjid Jami’ Al-Mujahidin Mosque Bintara, Bekasi Barat. The problem faced by the management of the Yayasan is the limited literacy related to the Yayasan's financial accounting standards and digital-based financial applications. Currently, the management has not implemented financial reporting based on ISAK 35. The management already has financial statements made manually. The method of these activities are training and socialization of digital-based financial report applications based on ISAK 35. Before and after the training, the pre-test and post-test were carried out related to training activities. The results of the activity shown that the training provided positive impacts that additional insights and understanding of the management related to financial reporting based on ISAK 35. In addition, the training provides digital literacy insights and makes it easier for the management to make financial reports. The trainees were satisfied with this community service activity. The target of this activity is that the Yayasan's management is able to apply digital-based financial statements based on ISAK 35 at the Yayasan Masjid Jami Al-Mujahidin.